Elections hinder firms' access to credit - Florian Léon; Laurent Weill (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
To analyze whether the occurrence of elections affects access to credit for firms, we perform an investigation using firm-level data covering 44 developed and developing countries. The results show that elections impair access to credit. Specifically, firms are more credit-constrained in election years and pre-election years as elections exacerbate political uncertainty. While lower credit demand is a tangible negative effect of elections, their occurrece per se does not seem to affect credit supply. We further establish that the design of political and financial systems affects how elections influence access to credit.
URN:NBN:fi:bof-202202091053
Keywords: G21; D72; O16; 330; elections; access to credit; credit constraints